2017
DOI: 10.1093/mnras/stx2773
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of the gravitational field generated by a random population of extended substructures

Abstract: A large population of extended substructures generates a stochastic gravitational field that is fully specified by the function p(F), which defines the probability that a tracer particle experiences a force F within the interval F, F + dF. This paper presents a statistical technique for deriving the spectrum of random fluctuations directly from the number density of substructures with known mass and size functions. Application to the subhalo population found in cold dark matter simulations of Milky Way-sized h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 83 publications
(125 reference statements)
2
24
0
Order By: Relevance
“…The other simulation denoted B N4096L400 ignored the effect of the free motion. The cosmological parameters are Ω 0 = 0.31, λ 0 = 0.69, h = 0.68, n s = 0.96, and σ 8 = 0.83, which are consistent with an observation of the cosmic microwave background obtained by the Planck satellite (Planck Collaboration et al 2014, 2016, 2018. The initial conditions were generated by a first-order Zeldovich approximation at z = 400.…”
Section: Initial Conditions and Numerical Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…The other simulation denoted B N4096L400 ignored the effect of the free motion. The cosmological parameters are Ω 0 = 0.31, λ 0 = 0.69, h = 0.68, n s = 0.96, and σ 8 = 0.83, which are consistent with an observation of the cosmic microwave background obtained by the Planck satellite (Planck Collaboration et al 2014, 2016, 2018. The initial conditions were generated by a first-order Zeldovich approximation at z = 400.…”
Section: Initial Conditions and Numerical Methodssupporting
confidence: 69%
“…Such steep cusps may have a significant effect on dark matter searches. There are a variety of subjects such as gravitational lensing (Chen & Koushiappas 2010;Erickcek & Law 2011;Van Tilburg et al 2018), Gravitational Waves (Bird et al 2016), Galactic tidal fluctuations (Peñarrubia 2018), gravitational perturbations on the Solar system (González-Morales et al 2013), pulsar timing arrays (Ishiyama et al 2010;Baghram et al 2011;Kashiyama & Oguri 2018) and indirect detection experiments (e.g., Berezinsky et al 2003;Koushiappas et al 2004;Koushiappas 2006;Goerdt et al 2007;Diemand et al 2007;Ando et al 2008;Ishiyama 2014;Bartels & Ando 2015;Fornasa & Sánchez-Conde 2015;Anderson et al 2016;Marchegiani & Colafrancesco 2016;Hütten et al 2016Hütten et al , 2018Hooper & Witte 2017;Moliné et al 2017;Stref & Lavalle 2017;Hiroshima et al 2018;Kamada et al 2019, and see also a recent review by Ando et al 2019). I14 showed that the steeper inner cusps of haloes near the free streaming scale can increase the dark matter annihilation luminosity of a Milky-Way sized halo between 12 % to 67 %, compared with the case we assume the NFW density profile (Navarro et al 1997) and an empirical mass-concentration relation proposed by Sánchez-Conde & Prada (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Summarising, the super-cool contribution dominates provided that T RH T dec . If DM interaction are small enough that it does not undergo kinetic recoupling, DM remains colder than in the freeze-out scenario: this has little observational implications [19]; the fact that supercool DM forms smaller structures could give enhanced tidal fluctuations possibly observable along the lines of [20]. The super-cool population of eq.…”
Section: Reheatingmentioning
confidence: 97%
“…Therefore, a ruling on the existence of low-mass ( 10 7 M ) dark matter subhalos would place strong constraints on the nature of dark matter (e.g., Bullock & Boylan-Kolchin 2017;Buckley & Peter 2017), which can be fur-arXiv:1811.03631v2 [astro-ph.GA] 13 Jun 2019 ther refined by measuring the minimum halo mass (e.g., Schmid et al 1999;Hofmann et al 2001;Loeb & Zaldarriaga 2005). Albeit dark, low-mass subhalos should still exert gravitational influence, for example, fluctuations of the gravitational tidal field are sensitive to the presence of subhalos down to 10 −6 M (Peñarrubia 2018). In a cosmological volume, however, gravitational lensing is our most sensitive method of detecting gravitational perturbations.…”
Section: Introductionmentioning
confidence: 99%